(untitled) - The American Oil Chemistry Society (New York, NY., 2004)
The book emphasizes modern techniques and recent advances in analytical chemistry using up-to-date instrumentation, it contains more than 420 methods including more than 100 added since 1989.
Keywords: Oils and fats,Oil industries,Oil analysis